The effect of elevated co2 on life cycle of Tenebrio molitor L. (COLEOPTERA: TENEBRIONIDAE) - Nur Hasyimah Ramli,; Salmah Yaakop,; Hakan Bozdoğan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tenebrio molitor L. (Coleoptera: Tenebrionidae) is a major pest of storage products and popularly used as a model species in biological research. This research is crucial in demonstrating the effects of increased CO2 in the environment. The objective of this study was to determine the effect of life cycle of T. molitor (F1) at two significance systems of CO2 namely Free Air CO2 Enrichment System (FACE) and Open Roof Ventilation Greenhouse System (ORVS). Each stage of T. molitor from 10 transparent plastic containers was observed every 2 days and recorded. Prolonged of complete life cycle on the T. molitor in ORVS (147-172days) observed with 43% delayed compared to FACE (71-84 days) and rearing room as control (RR) (77-105 days). The extension was due to prolong of larval to pupal development in ORVS (141-154 days), however, only 77-84 days in RR and FACE (71-84 days). The description of morphological changes in all stages and its coloration also recorded. This preliminary findings are important in predicting the T. molitor survivability due to climate variability and in strategizing the Integrated Pest Management (IPM) in the warehouses of storage products.